(untitled) (REDEL. Revista Granmense de Desarrollo Local, 2019)
An environmental management system gives some guidelines to ensure that an organization or company carries out all its activities in a way that is friendly to the environment. The dairy industry, due to its diversity of processes and products, generates a large amount of solid, liquid and gaseous waste, which can be seenincreased by improving productivity, quality and sanitation of them. The Dairy Products Company of Bayamo considers the development of the environmental management system to be appropriate, taking as reference the ISO 14001, since it is intended to carry out an appropriate handling of materials premiums and inputs of the organization. The Environmental Management was analyzed under the context of the impact that the food industry has on the environment with the aim of diagnosing the main environmental problems in the UEB ’’ Dieticians ’’, of the Dairy Products Company of Bayamo. The intention of this research was to propose an Environmental Management program based on what is established in three of the requirements of the NC 14001: 2004; in its sections: 4.2: Environmental policy; 4.3.1: Environmental aspects; 4.3.3: Objectives, goals and programs. It was carried outwithin the months of January 2018 and October 2018. In obtaining the information, theoretical and empirical methods were used, highlighting the survey and two main techniques: scientific observation (direct and indirect), documentary analyzes as well as the semi-standardized interview.